THE ROLE OF NURSING IN TRIAGE: FROM LITERATURE REVIEW TO CASE STUDY - Phan, Thị Hoài; Phạm, Văn Hiệp; Nguyễn, Thị Thanh Trà; Hoàng, Ngọc Phương; Nguyễn, Du Khánh; Nguyễn, Bích Hường; Phạm, Thị Hằng; Lê, Tự Minh Hoàng (Tạp chí Tai Mũi Họng Việt Nam, 2025)
Objective: To analyze nursing decisions and actions in clinical cases to strengthen the nursing role in triage of emergency patients. Method: Case study. Results: We describe a case of a patient with laryngeal dyspnea with the aim of highlighting the important role of nurses in early detection of signs of patient deterioration and timely implementation of coordinated emergency actions, contributing to ensuring safety and quality of care. Conclusion: Emphasize the indispensable role of nurses in triage of patients.